Characteristics of Student Learning Habits of Smokers - Jero Dwi Azrinas; Yusri Yusri (Jurnal Neo Konseling, 2021)
Habit is good one of the factors that support the achievement of student achievement. In fact there are still students who have bad habits in learning such as: not concentrating on taking lessons, not paying attention to the teacher when explaining lessons, and talking with friends when the teacher explains lessons, as well as going in and out of class when studying to smoke in stalls around the school This study aims to describe the characteristics of student smoking habits based on emotional, physical, cognitive, and motivational aspects. This research uses descriptive research with a quantitative approach. The research subjects were 50 boys who were obtained using purposive sampling technique. The results of this study indicate that the study habits of students at SMA Negeri 16 Padang are in the good category.